Vulneración de la calidad de crédito privilegiado de primera clase de los derechos del trabajador y del principio de cosa juzgada por el art. 89 del código del trabajo referente a la acción por colusión en reclamos laborales - Nole López, Betty Araceli (2015)
In the Ecuadorian juridical ordainment, beginning with our current Constitution of the Republic of the Ecuador approved by referendum in the year 2008, they settle down basic guarantees that aid the worker's rights, mainly for two reasons, the first one because they are right constitutional and fundamental for the economic, social and cultural development of the Ecuadorians. This way the Art. 33 of the Great Letter establish the right to the work like a right and duty, base of the national economy, and for this as much normative guarantees as the duty of political state tendencies have settled down to reduce the unemployment, underemployment and all precarious form of labor recruiting. For disposition of the Art. 326 numeral of the Constitution, the worker's rights are inalienable and re, and for this any authority either administrative or judicial, it can harm these prerogatives. Likewise they protected the rights of the workers the Art. 88 of the Code of the Work that its gives them the category of privileged credits and for this they have preference in the payment order when there is more worthy of employer, but a legal deficiency exists in the Art. 89 of the same normative body, because it allows third creditors to retain the product of the one it finishes off that it should be canceled the worker by virtue of their preferable credit, to consider that collusion exists in the labor birdcall. A case of collusion in a labor process is very difficult that happens, because according to the Oral Procedure that establishes the Code of the Work, so that sentence is dictated it should have two audiences, the first one in which the reconciliation, answer at the demand and test announcement, and the second is looked for where you receipts the testimonial test and the allegations of the parts. But in case if collusion exists, it should be processed in via separate, because it is that attempts to the labor rights the one that one can request the retention of the seizure for third creditors' suspicions, when it has already concluded the stages of the process, the sentence is firm and the failure has already been executed.